Extralabel mastitis therapy: what does it mean? - J.R. Roberson (Kansas Agricultural Experiment Station Research Reports, 2001)
Extra-label drug use (ELDU) is needed to provide optimal therapy for ill dairy cattle. Proper ELDU requires cooperation and compliance between the veterinarian and producer to ensure that proper drug withdrawal times are observed.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Regulations; Mastitis